A Novel Design & Fabrication of Energy Generating Oscillatory Swing – A Play way Technique for Public Parks. (2017) - Yathavan, S.; Kumar, G. Ramesh; Gokulraj, S.
Abstract: A novel electrical energy generating oscillatory children play swing has been designed and fabricated for the effective utility of public parks. The energy producing swing works on the principle of lever mechanism. The connected freewheels fitted with swing bar rotates the wheel arrangement which is annexed to the vertical bar. Whenver, the main wheel rotates, a synchronous movement of a dynamo generates electricity and simultaneously stored in a chargeable battery. The output power can be fed to lighting bulbs of public parks as well as for charging communication devices like mobile phones, electronic toys, etc., The details of output delivered by the units have been discussed in detail.